Borderlands: The new mestiza - Anzaldúa, Gloria (Spinsters, Aunt Lute, 1987)
Rooted in Gloria Anzaldúa’s experience as a Chicana, a lesbian, an activist, and a writer, the groundbreaking essays and poems in this volume profoundly challenged how we think about identity. Borderlands/La Frontera remapped our understanding of what a “border” is, seeing it not as a simple divide between here and there, us and them, but as a psychic, social, and cultural terrain that we inhabit, and that inhabits all of us. This twentieth-anniversary edition features new commentaries from prominent activists, artists, and teachers on the legacy of Gloria Anzaldúa’s visionary work
Le texte « La conciencia de la mestiza : Toward a New Consciousness » a été donné en lecture au cours POL4212.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme décolonial; identités LGBTQIA2+; lit3220; littérature; mexique; pol4212; premier cycle; queer; régions géographiques; thématiques; états-unis; études littéraires

Il n'y a pas de cogito-femme - Collin, Françoise (L'émergence d'une culture au féminin, 1987)
Keywords: 1900-1999; 1980-1989; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem9000; histoire et politique; interdisciplinarité; philosophie; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; thématiques; études culturelles; études littéraires

Reading black, reading feminist: A critical anthology - Gates, Henry Louis (Meridian Book, 1987)
A unique and comprehensive collection of 26 literary essays that provides real evidence of the rich cultural history of black women in America. Black women’s writing has finally emerged as one of the most dynamic fields of American literature. Here, leading literary critics—both male and female, black and white—look at fiction, nonfiction, poetry, slave narratives, and autobiographies in a totally new way. In essence, they reconstruct a literary history that documents black women as artists, intellectuals, symbol makers, teachers, and survivors. Important writers whose work and lives are explored include Toni Morrison, Gloria Gaynor, Maya Angelou, and Alice Walker, and the fascinating list of essays range from Nellie Y. McKay’s “The Souls of Black Women Folk in the Writings of W. E. B. Du Bois” to Jewelle L Gomez’s very personal tribute to Lorraine Hansberry as a dramatist and crusader for social justice. Henry Louis Gates Jr., the editor of this anthology and a noted authority on African-American literature, has provided a thought-provoking introduction that celebrates the experience of “reading black, reading feminist.” A penetrating look at women’s writing from a unique perspective, this superb collection brings to light the rich heritage of literary creativity among African-American women.
Keywords: 1900-1999; afro-féminisme; amériques; anthologie; approches et analyses; cours; discipline; fem1000; femmes* noires; féminismes noirs; pratiques féministes; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires

La création musicale chez les religieuses de trois communautés montréalaises - Rhéaume, Claire (Université de Montréal, 1987)
https://bibliomontreal.uqam.ca/bibliographie/notice/SFB8PZRP
Keywords: DIG; amériques; arts; discipline; montréal; musique; mémoires/thèses; régions géographiques; soeurs de sainte-anne; soeurs de sainte-croix; soeurs des saints noms de jésus et de marie